2009
DOI: 10.1111/j.1741-3737.2009.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive Marital Quality, Acculturative Stress, and Child Outcomes Among Mexican Americans

Abstract: Positive Marital Quality, Acculturative Stress, and Child Outcomes Among Mexican AmericansPrevious research suggests that the quality of parents' relationships can influence their children's adjustment, but most studies have focused on the negative effects of marital conflict for children in White middle-class families. The current study focuses on the potential benefits of positive marital quality for children in working-class first generation Mexican American families using observational and self-report data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 63 publications
5
39
1
2
Order By: Relevance
“…These factors are along the lines of previous studies in that pupils of immigrant mothers may perform worse than those of native mothers (e.g., Fernandez-Kelly and Schauffler, 1994; Jain and Belsky, 1997; Leidy et al, 2009;Van Amersfoort, 1974;Rosenthal et al, 1983;Lareau, 1989;Rong and Grant, 1992;Cosden et al, 1995;Kao and Tienda, 1995). The point is that the ineffective learning of pupils with immigrant mothers does not pertain to the pupils themselves, but can be attributed to their feeling that they are not treated in a "seems fair" environment.…”
Section: Resultssupporting
confidence: 73%
“…These factors are along the lines of previous studies in that pupils of immigrant mothers may perform worse than those of native mothers (e.g., Fernandez-Kelly and Schauffler, 1994; Jain and Belsky, 1997; Leidy et al, 2009;Van Amersfoort, 1974;Rosenthal et al, 1983;Lareau, 1989;Rong and Grant, 1992;Cosden et al, 1995;Kao and Tienda, 1995). The point is that the ineffective learning of pupils with immigrant mothers does not pertain to the pupils themselves, but can be attributed to their feeling that they are not treated in a "seems fair" environment.…”
Section: Resultssupporting
confidence: 73%
“…When using a theory in an article, it would be better to make references to the theory in both the introduction and discussion sections. Some researchers use theories in the introduction section to guide their research but fail to discuss the results in light of the theory they used (i.e., Leidy, Parke, Cladis, Coltrane, & Duffy, 2009). Adversely, some researchers only mentioned the theory on their discussion section but not in their introduction section (i.e., Davila, McFall, & Cheng, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Thumboo et al (2000) suggested that the two factors corresponding to the MFM may be merged into a common factor based on the principle of parsimony. However, other researchers suggested the possibility of separate positive and negative dimensions of marital quality (Cladis et al 2009; Fincham and Linfield 1997; Mattson et al 2007). The moderate correlation between the two factors suggests that they may be conceptually distinct but related dimensions representing couples’ evaluations of the intimacy and conflict aspects of their marital relationship.…”
Section: Discussionmentioning
confidence: 99%